Higher Predictive Value Positive for MMA Than ACA MTM Eligibility Criteria Among Racial and Ethnic Minorities: An Observational Study - Yanru Qiao MS; Christina A. Spivey PhD; Junling Wang PhD; Ya-Chen Tina Shih PhD; Jim Y. Wan PhD; Julie Kuhle BS; Samuel Dagogo-Jack MD; William C. Cushman MD; Marie A. Chisholm-Burns PharmD, MPH, MBA (SAGE Publishing, 2018)
The objective of this study was to examine positive predictive value (PPV) of medication therapy management (MTM) eligibility criteria under Medicare Modernization Act (MMA) and Affordable Care Act (ACA) in identifying patients with medication utilization issues across racial and ethnic groups. The study analyzed Medicare data (2012-2013) for 2 213 594 beneficiaries. Medication utilization issues were determined based on medication utilization measures mostly developed by Pharmacy Quality Alliance. MMA was associated with higher PPV than ACA in identifying individuals with medication utilization issues among non-Hispanic blacks (blacks) and Hispanics than non-Hispanic whites (whites). For example, odds ratio for having medication utilization issues to whites when examining MMA in 2013 and ACA were 1.09 (95% confidence interval [CI] = 1.04-1.15) among blacks, and 1.17 (95% CI = 1.10-1.24) among Hispanics, in the main analysis. Therefore, MMA was associated with 9% and 17% higher PPV than ACA in identifying patients with medication utilization issues among blacks and Hispanics, respectively, than whites.